Assessment of Depression Severity and its Impact on the Quality of Life among Parents of Pediatric Patients with Clubfoot: A Cross-Sectional Study - Sohail, Hafiza Samavia; Khan, Hassan; Khalil, Muhammad Huzaifa; Haider, Tehrim; Muskan, Rahiya; Asad, Khursheed; Khalid, Wishal (Indus Journal of Bioscience Research, 2025)
Background: Clubfoot is a congenital musculoskeletal condition that needs a prolonged treatment protocol. Parents face psychological challenges such as depression, which can adversely affect their quality of life and impair their caregiving abilities. Objective: The purpose of this study is to determine the severity of depression among parents of children with clubfoot and its effect on their quality of life using validated psychometric tools such that DASS-21 and SF-36. Methodology: A cross-sectional study was conducted at the Paraplegic Center in Peshawar, Pakistan, between November 2024 and April 2025. Non-probability convenience sampling was used to recruit 196 parents of pediatric clubfoot patients. The DASS-21 was used to assess depression, and the SF-36 Health Survey to assess quality of life. The CUSIT Research Committee gave ethical approval after receiving informed consent. Results: Data analysis was done through IBM SPSS version 24. The average depression score among participants was moderate (M= 18.80, SD = 10.25), and the mean QoL score indicated a moderate level of well-being (M = 54.85, SD = 16.94). A strong negative correlation (r = –0.906, p < 0.001) was found between depression and quality of life. Linear regression analysis confirmed that 83% of the variance in QoL scores could be attributed to depression severity (R² = 0.830), establishing depression is a strong predictor. Upon SPSS gender- specific analysis, results show that depression scores were higher in female parents (mothers) and significantly lower quality of life compared to male parents (p < 0.005). Significantly, 11.6% of mothers fell in the “extremely severe” category of depression, while the percentage of fathers was 3.6%. Conclusion: The study highlights a significant connection between depression and quality of life among parents of children with clubfoot. These psychological challenges are particularly more prominent in mothers, highlighting the need for gender-specific interventions.